The Perception and Characteristics of Tourists in Semarang City - Fafurida Fafurida; Frida Apriliani (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The purpose of the study is to find out the conditions and the quality of tourist destinations in Semarang, the characteristics of tourists, and the pattern of foreigners in Semarang. The population of the study is the tourists of Semarang in 2016 which are as much as 3.125.197 tourists. The samples of the study are 400 tourists taken by using the Slovin formula with convenience sampling. The study is used a quantitative descriptive approach. The data collection is used the questionnaires. The techniques data analysis is used descriptive statistics. The results of the study show that the tourists perception toward the quality of tourist destinations in a tourist attractions of Semarang based on attraction aspects, facilities and accessibility in 2018, most of them are gave good enough opinion. The characteristics of tourists that visited Semarang in 2018, most of them are domestic tourists, men, between 18-40 years old, were not married yet, they came from another city, their last education is highchool/equal, and they are students/students college.The pattern of tourists visiting the tourist attractions in Semarang in 2018 is most of the tourist came with their family/friends in order to vacation/recreation, the visits frequency only once in a year for 1-2 days and most of them came in the day of Eid al-Fitr holiday. Based on secondary data, Semarang has three times peak seasons, those are new year masehi, school day off and Raya Eid al-Fitr holiday.